(untitled) (Nepal Medical College Journal, 2020)
More than 50% of the world’s population has at least a thyroid nodule. Detail clinical examination and radiology may help in diagnosing thyroid lesions but the management depends upon the cytopathological diagnosis. Optimum use of fine needle aspiration cytology (FNAC) and better understanding of cytomorphological characteristic of thyroid lesions by using Bethesda system, triaging of patients who are to be treated medically or surgically is more accurate. The objective of this present study is cytopathological evaluation of thyroid lesions based on Bethesda System in patients attending Birat Medical College and Teaching Hospital. The objective was also to correlate the cytological findings with histopathological findings where ever possible. A total of 104 patients with thyroid lesions underwent fine needle aspiration cytology in a period of a year (September 1, 2019 to August 31, 2020). Cytological features were evaluated and classified according to the Bethesda system. Histopathological features were evaluated and correlated wherever available. Among 104 patients with thyroid lesions 93 were female and 11 were male. Four cases turned out to be non diagnostic, 85 benign, three Atypia of undetermined significance, three Suspicious for follicular neoplasm and eight Suspicious of malignancy and one Malignant according to Bethesda system. Histopathology specimen was received in 31 patients out of whom 20 (64.5%) patients were reported as colloid nodule, two follicular adenoma, one Hurthle cell adenoma, six papillary carcinoma and two follicular carcinoma. Medullary carcinoma and anaplastic carcinoma were not seen in the patients evaluated. Specificity and sensitivity of fine needle aspiration cytology was 94.7% and 88.9% respectively. Thus reporting thyroid lesions FNAC with Bethesda system allow a more specific cytological diagnosis.